Spatial distribution of fine-grained floodplain deposits and anthropogenic materials based on official borehole data in the floodplain of Leipzig, Germany - Nele Graubner; Johannes Schmidt (PANGAEA, 2024)
This data set contains data representing the thickness and spatial distribution of fine-grained floodplain deposits and anthropogenic material in the Leipzig floodplain area. It includes four raster layers (.tif format): one showing the interpolated distribution of the top level of fluvial gravel deposits in the floodplain and one showing the top level of fluvial gravels. The third raster layer presents the thickness of fine-grained floodplain deposits. Additionally, the stratigraphic data was used to spatially model the distribution of thickness of the anthropogenic material in the research area. A shapefile is provided, containing processed data from 3,414 drillings used to develop the spatial model. The data set originates from drilling records provided by the Saxon State Office for Environment, Agriculture, and Geology (LfULG) which were filtered and categorized by their stratigraphical characteristics. Further information on methodological details is described in Graubner and Schmidt (2024) - Data in Brief.